Disruption: A Collection of Narrative Profile about the Stigma and Discrimination of Mental Illness on Senior High School Students - Gomez, James Garreth (Animo Repository, 2022)
This study summarizes the stigma and discrimination being experienced by young adults and acknowledges areas wherein research is needed to identify the factors that contribute to this matter. The following questions are addressed: (1) What kind of stigma and discrimination do these teenagers with depression and/or an anxiety disorder experience? (2) How can the stigma and discrimination of mental illness be portrayed through the particularities of the narrative profile? (3) What techniques will be used for the narrative profile that may effectively portray lived experiences and raise awareness? A collection of narrative profile essays was established for this research for it required critical discourse on the subject that included a more comprehensive study. The usage of research and development of the profile essay requires different perspectives, extensive details, and how the stigma is being developed. Further examination of the discourse will be shown with the use of a narrative profile essay, which will benefit society regarding mental illness awareness.